Ulcerative Colitis in Patients Presenting with Bleeding Per Rectum (Medical Forum Monthly, 2024)
Objective: To determine the frequency of ulcerative colitis in patients presenting with bleeding per rectum.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Gastroenterology Shiekh Zayed Hospital, Lahore from 10-03-2024 to 10-09-2024.Methods: After approval of the synopsis, consent was taken from ethical review committee of the hospital. After that 95 patients fulfilling the inclusion criteria was assessed for socio-demographic and clinical data recorded on a pre-designed proforma. Then these cases were undergo colonoscopy by a consultant gastroenterologist and biopsy was taken under direct vision and ulcerative colitis was labeled as per operational definition. All these results were collected and recorded on same proforma.Results: Total of 95 patients, 67.4 %( n=64) were in age group of 20-40 years and 32.6 %( n=31) were in age group of 41-60 years and mean age was calculated as 37.43±7.85 years. There were 64.2 %( n=61) were male whereas 35.8 %( n=34) were females. Frequency of ulcerative colitis in patients with bleeding per rectum was 27.4 %( n=26).Conclusion: Current study found that frequency of ulcerative colitis was 27.6% in patients with bleeding per rectum and there was no significant association of ulcerative colitis with diabetes mellitus and smoking.